Optimalisasi Kualitas Personil Jaga Di Anjungan Agar Terjamin Keselamatan Di Atas Kapal - Aberaldo Fransisco Bakari, Aberaldo; Yosis Onasis; Santun Irawan (Politeknik Pelayaran Sulawesi Utara, 2022)
The background of this research is the incident that occurred on a ship that experienced problems crossing with other ships in early December 2022 the MV ship, Charlotte was sailing from the loading port in Marunda (North Jakarta) to the unloading port in Palembang. At the time of the change of guard from the second officer on guard duty at 00.00-04.00 with the first mate on guard duty at 04.00-08.00, at that time the ship was in TSS towards the unloading port. In Marunda there is a tugboat that is towing a barge loaded with wood that will cut the TSS from the right side of MV Charlotte's hull. By viewing the tugboat's three parallel white lights it can be identified that the ship is less than 6 Nautical Miles away. To be sure, at that time the second mate checked through radar and it turned out that the distance from the MV Charlotte to the tugboat was 5.5 Nautical Miles. At the time of the second handover of the guard with the first mate by showing the surrounding conditions and notifying that there was a tugboat that would cut in front of the bow which was still 5.5 Nautical Miles away. Maybe because the first mate was not yet conscious because he was still sleepy, he just said